2017
DOI: 10.18203/2394-6040.ijcmph20170291
|View full text |Cite
|
Sign up to set email alerts
|

Role of knowledge and attitude in determining standard precaution practices among nursing students

Abstract: Background: Standard precaution practice (SPP) is aimed at protecting both patients and health professionals alike. The high rate of occupational hazards among health workers especially in developing countries is counterproductive and therefore requires thorough investigation and intervention. This study aims to determine the role of knowledge and attitude in determining SPP among nursing students.Methods:This research involved 172 nursing students at the teaching hospital of University of Maiduguri. Sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This study also found that there was no significant linear correlation between knowledge and compliance of practice towards standard precautions among nursing students. Contradict with a study by Balami et al (8) which established the role of knowledge as a determinant of standard precaution practice among undergraduate nursing students and despite the poor knowledge of infectious diseases, the participants still demonstrated an acceptable level of self-reported practice of SP. However, the impact of knowledge on the practice of health care personnel has been debated and concluded in a different view (11,13,23,24).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study also found that there was no significant linear correlation between knowledge and compliance of practice towards standard precautions among nursing students. Contradict with a study by Balami et al (8) which established the role of knowledge as a determinant of standard precaution practice among undergraduate nursing students and despite the poor knowledge of infectious diseases, the participants still demonstrated an acceptable level of self-reported practice of SP. However, the impact of knowledge on the practice of health care personnel has been debated and concluded in a different view (11,13,23,24).…”
Section: Discussionmentioning
confidence: 85%
“…Nurses need to protect themselves, the patients, and relatives from any form of hospital-acquired infections hence the need to practice SP (7). Besides, nursing students on the other hand are also more vulnerable to any form of hospital-acquired infectious during training skills and acquisitions (8). Nursing students are often exposed to various infections during their clinical education or training and they have a responsibility to protect themselves (9).…”
Section: Introductionmentioning
confidence: 99%
“…Then again are significantly progressively vulnerable to secure contamination during preparing and aptitude accomplishment. On the off chance that they won't appropriately get addresses on standard detachment safeguards from their clinical and scholarly educators in the beginning of their session just as before allocating of month to month clinical obligations they can't secure legitimate information of standard disengagement safety measures (Balami, Ismail, Saliluddin, & Garba, 2017).…”
Section: Introductionmentioning
confidence: 99%